The design of tractor CAN bus intelligent node based on dual-core processor. (2015) - Cao, Qingmei; Zhou, Zhili
This paper, based on the development of tractor CAN bus control network and on the study of ISO11783 protocol, studies the communication between ECU of tractors. The communication between tractor slip rate measuring sensor and power shift transmission is treated as an example to illustrate the application of CAN bus technology. The design scheme, which is based on dual-core processor MC9S12XD, for software and hardware of intelligent communication nodes on the tractor CAN bus network is presented. By combining the advantages of dual-core technology and CAN bus, the efficiency of information transfer and system response speed is improved.